THE INFLUENCE OF STUDENTS’ PERCEPTION ON SCHOOL INVIRONMENT AND PARENTING STYLE TOWARDS ENGLISH LEARNING ACHIEVEMENT - Zubaidah Zubaidah; Oom Rohmah Syamsudin (INFERENCE: Journal of English Language Teaching, 2018)
Abstract: effects of  students perception for school evironment and parenting toward english academic achievement.  The expanatory survey method was aimed at describing the effects of students perception of students for school environment and parenting toward english academic achievement. From the population of all the students of Governmet Junior High Schools  in Citeureup Bogor Jawa Barat (820 people), a sampel of 90  students were randomly selected. The data were collected using a questionnaire and then  analyzed statistically using regretion SPSS 22.0 analyses. The results showed that school evironment and parenting  influential toward english academic achievement. Keywords: English academic achievement, School evironment, parenting Abstrak: pengaruh persepsi siwa atas lingkungan sekolah dan pola asuh orang tua terhadap prestasi belajar bahasa Inggris. Penelitian ini  bertujuan mengetahui pengaruh persepsi lingkungan sekolah dan pola asuh orang tua terhadap prestasi belajar bahasa Inggris. Penelitian mengunakan metode survey, dengan populasi siswa SMP Negeri di Citeureup kabupaten Bogor Jawa Barat. Dengan teknik sampling acak proporsional dipreroleh sampel sebesar 90 orang. Teknik anallisis regresi dengan mengunakan program aplikasi SPSS 22.0. hasil penelitian membuktikan bahawa lingkungan sekolah dan pola asuh berpengaruh terhadap presatasi belajar bahasa Inggris. Kata Kunci: Prestasi  belajar bahasa Inggris, lingkungan sekolah, pola asuh